2011
DOI: 10.1091/mbc.e10-12-0953
|View full text |Cite
|
Sign up to set email alerts
|

The SUMO-specific isopeptidase SENP2 associates dynamically with nuclear pore complexes through interactions with karyopherins and the Nup107-160 nucleoporin subcomplex

Abstract: We determined that the small, ubiquitin-related modifier–specific isopeptidase, SENP2, is dynamically associated with nuclear pore complexes (NPCs). This association is determined by the activities of three N-terminal signals in SENP2: a high-affinity nuclear localization sequence, an Nup107-160–binding element, and a nuclear export signal. NPC association, and its potential regulation, affects SENP2 accessibility to substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 56 publications
4
70
0
Order By: Relevance
“…4A). SENP1 was depleted by ϳ90%, whereas each of the three major isoforms of SENP2 recognized by our antibody (30) were depleted by ϳ70 -80%. Under these knockdown conditions, SENP1 depletion uniquely increased the ratio of SUMO-mod- ified to unmodified TDG.…”
Section: Resultsmentioning
confidence: 79%
“…4A). SENP1 was depleted by ϳ90%, whereas each of the three major isoforms of SENP2 recognized by our antibody (30) were depleted by ϳ70 -80%. Under these knockdown conditions, SENP1 depletion uniquely increased the ratio of SUMO-mod- ified to unmodified TDG.…”
Section: Resultsmentioning
confidence: 79%
“…Interestingly, overexpression of SENP2 led to cell cycle arrest at the prometaphase stage, caused by defects in targeting the microtubule motor protein CENP-E to kinetochores [34]. Several studies showed that the N-terminal domains of SENP proteases determine their subcellular localization and interaction partners [35][36][37]. Indeed, a comparison between different chimeric fusion proteins of SENP1 and SENP2 revealed that the N-terminus of SENP2 is essential for its unique features.…”
Section: Redistribution Of the Sumo Machinery During Mitosismentioning
confidence: 99%
“…In most cell types, SENP1 is predominantly nuclear (e.g., Bailey and O'Hare 2004;Gong et al 2000;Itahana et al 2006). In contrast, SENP2, like yeast Ulp1, is associated with the nuclear face of the nuclear pore complex (Goeres et al 2011). Both SENP1 and SENP2 move between the nucleus and the cytoplasm (Goeres et al 2011;Kim et al 2005).…”
Section: Localisationmentioning
confidence: 99%
“…In contrast, SENP2, like yeast Ulp1, is associated with the nuclear face of the nuclear pore complex (Goeres et al 2011). Both SENP1 and SENP2 move between the nucleus and the cytoplasm (Goeres et al 2011;Kim et al 2005). This relocalisation is dependent on interactions with proteins associated with the nuclear pore complex as well as nuclear localisation sequences (NLSs) and nuclear export sequences (NESs) (Chow et al 2012;Goeres et al 2011;Itahana et al 2006;Kim et al 2005).…”
Section: Localisationmentioning
confidence: 99%